ROI for technology projects : measuring and delivering value. - Roulstone, D. Brian, ....-; Phillips, Jack J., 1945- (Amsterdam : Elsevier, 2008)
ROI for Technology Projects: Measuring and Delivering Value presents a proven Return on Investment (ROI) Methodology, based on almost 20 years of development and improvement. It is a process that is rich in tradition and refined to meet the demands facing IT and technology development projects. With increased scrutiny of technology spending by the most complex organizations in the world, ROI has become one of the most challenging and intriguing issues facing the Information Technology sector. The profession requires a rational, logical approach that can be simplified and implemented within the current budget constraints and resources of the organization. This is the first book of its kind to do just that and is written by two experienced authors in the field. Practical and well-structured ROI for Technology Projects: Measuring and Delivering Value provides a framework and method that can ensure greater success in mobilizing technology initiatives. Written for managers and executives who are tasked with implementing and executing key technology projects and initiatives within their organizations. It will also be of interest to technology consultants, business analysts, and practitioners who are responsible for scoping, designing, and implementing key technology initiatives within organizations.
Keywords: Return on investement ; verandermanagemement